The prediction of coronary artery disease based on non-invasive examinations and heme oxygenase 1 polymorphism versus virtual histology - Kovarnik, Tomas; Kral, Ales; Skalicka, Hana; Mintz, Gary S; Kralik, Lubomir; Chval, Martin; Horak, Jan; Skalicka, Lenka; Sonka, Milan; Wahle, Andreas; Downe, Richard W; Uhrova, Jana; et al. (The Journal of invasive cardiology, 2013)
OBJECTIVE: Prediction of coronary atherosclerosis in patients with stable angina based on non-invasive examinations. METHODS: Pro-inflammatory markers, heme oxygenase-1 (HO-1) polymorphism, lipid levels, Framingham risk score (FRS), and carotid ultrasound were analyzed and compared to grayscale and virtual histology intravascular ultrasound (VH-IVUS). RESULTS: A total of 101 patients were included, and genetic analysis was performed on 81 patients (80.2%). The HO-1 risk polymorphism was more frequent in patients post-myocardial infarction (61.3% vs 32%; P=.0097), or with diabetes (68.4% vs 35.5%; P=.011) or a higher FRS (21.5 vs 15.7; P=.014). Plaques in patients with the HO-1 risk polymorphism contained less fibro-fatty tissue (17.1% vs 23.2%; P=.005) and more necrotic core (NC; 17.1% vs 12.7%; P=.02) and calcification (10.2% vs 5.7%; P=.035) compared to patients without the HO-1 risk polymorphism. Carotid intima media thickness (P=.05) and carotid bulb plaque (P=.008) predicted plaque burden. The level of Apo A inversely correlated with NC (P=.047; r = -0.27) and was lower in patients with VH-thin-cap fibroatheroma (VH-TCFA; 1.19 mmol/L vs 1.3 mmol/L; P=.04). FRS correlated with NC (P=.007; r = 0.2), with angiographic disease severity (P=.032; r = 0.21) and was higher in patients with VH-TCFA (9.1 vs 7.8; P=.03). CONCLUSION: Carotid ultrasound and HO-1 polymorphism improve coronary atherosclerosis prediction.
Keywords: apolipoproteiny A; Female; nemoci arterie carotis; biologické markery; Carotid Intima-Media Thickness; Biomarkers; Angina, Stable; ženské pohlaví; Predictive Value of Tests; prediktivní hodnota testů; lidé; genetická predispozice k nemoci; Genetic Predisposition to Disease; intimomediální šíře tepenné stěny; Physical Examination; hemoxygenasa-1; Risk Factors; nemoci koronárních tepen; Male; Aged; Carotid Artery Diseases; polymorfismus genetický; Coronary Artery Disease; fyzikální vyšetření; rizikové faktory; Heme Oxygenase-1; lidé středního věku; stabilní angina pectoris; senioři; mužské pohlaví; Apolipoproteins A; Polymorphism, Genetic; Middle Aged; Humans